1984
DOI: 10.1111/j.2044-8325.1984.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Selecting trainee conference interpreters: A preliminary study

Abstract: This study developed and assessed a set of psychometric tests to aid selection of candidate simultaneous and consecutive interpreter trainees. Three kinds of test were used based either on text materials, linguistic subskills or speed stress Twelve tests in all were administered to 29 trainees beginning an intensive course. The test scores were correlated with judges' ratings in the final interpreting examination. Students who passed the examination had higher mean scores on all tests than those who failed (si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 4 publications
2
24
0
1
Order By: Relevance
“…aspirations and for the Interpreting Schools to optimise their human and financial resources have spurred many efforts to devise and implement selection practices (Gerver et al 1984, Gran and Dodds 1989, Lambert 1992, Arjona-Tseng 1994, Moser-Mercer 1994. Intuition and experience amongst professionals and/or trainers indicate that basic pre-requisites of a good professional interpreter are: profound knowledge of active and passive languages and cultures, ability to grasp the original meaning quickly and to convey the essential meaning of what is being said, ability to project information with confidence, coupled with good voice, wide general knowledge and interests and, finally, ability to work as a member of the team (Gerver et al 1984, Lambert 1992.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…aspirations and for the Interpreting Schools to optimise their human and financial resources have spurred many efforts to devise and implement selection practices (Gerver et al 1984, Gran and Dodds 1989, Lambert 1992, Arjona-Tseng 1994, Moser-Mercer 1994. Intuition and experience amongst professionals and/or trainers indicate that basic pre-requisites of a good professional interpreter are: profound knowledge of active and passive languages and cultures, ability to grasp the original meaning quickly and to convey the essential meaning of what is being said, ability to project information with confidence, coupled with good voice, wide general knowledge and interests and, finally, ability to work as a member of the team (Gerver et al 1984, Lambert 1992.…”
mentioning
confidence: 99%
“…Intuition and experience amongst professionals and/or trainers indicate that basic pre-requisites of a good professional interpreter are: profound knowledge of active and passive languages and cultures, ability to grasp the original meaning quickly and to convey the essential meaning of what is being said, ability to project information with confidence, coupled with good voice, wide general knowledge and interests and, finally, ability to work as a member of the team (Gerver et al 1984, Lambert 1992. The purpose of our research is to investigate the second pre-requisite, i.e., the cognitive-linguistic component.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding their diversity, some general trends can be detected and will be tackled in greater detail in the relevant sections of the present paper. Some authors with an interpreting background collaborated with scholars from other disciplines, such as psychology, to develop multi-component testing batteries which they described in detail (Gerver et al 1984). Others drew inspiration from different disciplines to suggest tests based on those findings: the test based on research into foreign language acquisition suggested by Carroll (1978), the shadowing 4 test described by Lambert (1992a) and the test on personality traits described by Schweda Nicholson (2005).…”
Section: What To Look For In An Interpreting Candidatementioning
confidence: 97%
“…Ud fra et stort antal artikler skrevet af professionelle tolke og tolkelaerere finder Gerver (1984) frem til 5 vaesentlige forudsaetninger for at kunne udføre et tilfredsstillende arbejde som simultantolk: 1) Dybtgående aktivt og passivt kendskab til sprog og kultur. 2) Evne til hurtigt at opfatte og omsaette det vaesentlige i et budskab.…”
Section: Skal Der Saerlige Egenskaber Til For At Blive Simultantolk?unclassified